Political participation in high social vulnerability contexts: an exploratory study in a community of Porto Alegre, Brazil - Costa, Pedro de Almeida (Revista de Administração da UFSM, 2015)
This paper is under the field of Social Social studies and aims to discuss if the apparent political apathy of a socially vulnerable community is a condition to be overcome or if such condition means an inability to dialogue with the cultural matrix values ​​from which come modern Western rationality and its concepts. This questioning is made from the dialogue between empirical data from an ethnographic research with two years' duration, held in a community with such characteristics, and theoretical foundation which seeks to discuss what could be the causes of a perverse reproduction of unequal conditions in a country of peripheral modernity, especially from the notion of undercitizenship. The initial reflections on this subject point out that such a concept can explain, even in part, the difficulty of people in becoming effective political actors capable of fighting and demand change in its own condition, despite public policies designed to overcome this condition.